Philippines Economic Update, October 2018 : Staying in the Course Amid Global Uncertainty - World Bank (World Bank, Washington, DC, 2018)
The Philippines’ economic growth outlook remains positive, yet downside risks have increased. An expected slowdown in global trade in the medium term is likely to further dampen Philippine exports. Nevertheless, baseline economic growth is projected at 6.5 percent in 2018, 6.7 percent in 2019, and 6.6 percent in 2020. The baseline investment growth outlook is positive and planned senatorial and local elections in May 2019 are expected to lead to higher public spending and higher private consumption. However, persistent high domestic inflation could have a dampening effect on consumption and investment growth. Also, a faster normalization of monetary policy in the United States and an increase in global uncertainty, including trade tensions, could not only worsen external financing conditions for emerging market economies like the Philippines but also elicit additional domestic interest rate hikes that could raise domestic borrowing costs for businesses and households.